Salt taste threshold and sodium intake on the incidence of hypertension in adults in Depok, West Java - Adhila Fayasari; Safira Indri Cahyani (Universitas Teuku Umar, 2022)
Hypertension is one of the most non-communicable diseases in Indonesia. The prevalence of hypertension in Indonesia is 25.8% based on measurements at age ≥ 18 years. One of the factors that influence the occurrence of hypertension is sodium intake and several studies have shown that there is a relationship between hypertension and salt taste threshold. This study aimed to analyse the relationship between salt taste threshold and sodium intake with the incidence of hypertension at the age of 18-60 years in the Cimanggis District Health Center, Depok City in 2019. This study used a case control design of outpatients in the Cimanggis District Health Center, Depok City. Subjects were selected by purposive sampling technique. Data characteristics were collected using administered questionnaire. Sodium intake was measured using the SQ-FFQ, and salt taste threshold was measured using the Khobragade method, with 5 variation of sodium concentration. Sodium intake in the case group was higher than the control group, with an average sodium intake in the case group of 2,620 mg and in the control group of 2,100 mg. The taste threshold in the case group increased by 20% while in the control group as much as 12%. There was no significant relationship between salted taste threshold and the incidence of hypertension, but there was significant relationship between sodium intake and hypertension.